Co-production in HIV research: a case study from the COVID-19 pandemic - Vasiliki Papageorgiou; Jane Bruton; Halle Johnson; Silvia Petretti; Wezi Thamm; Joshua Anderson; Husseina Hamza; Helen Ward (Research Involvement and Engagement)
Abstract Background Co-produced research is an approach where people with lived experience voluntarily engage as collaborators throughout the entire research process. In this study, academic researchers aimed to recruit and train people living with HIV, in partnership with a community-based organisation (Positively UK), with the objective of enhancing research skills and capabilities of the HIV community to lead and/or facilitate forthcoming research initiatives and projects. Main body Our collaborative endeavour involved a group of academic researchers, a public involvement practitioner and people living with HIV (comprising two co-researchers and three advisory group members) to design and conduct a participatory, qualitative enquiry from January to September 2021. Our study aimed to explore the experiences of people living with HIV within the United Kingdom during the COVID-19 pandemic. All co-researchers underwent rigorous and essential research training that encompassed ethics, conducting qualitative interviews, analysing transcripts and considerations pertaining to emotional well-being. Communication was conducted exclusively by phone or online throughout the project. The unpredictability associated with the pandemic necessitated an adaptive and flexible approach that encompassed personal circumstances and the intricacies of conducting research during a global health crisis. Based on our reflections, we map out our collaborative experiences and provide recommendations for the advancement of future co-produced research endeavours involving people living with HIV at each stage of the research cycle. We identify four areas of focus: (1) building relationships inclusive of trust and rapport and managing stakeholders’ expectations; (2) reciprocal learning and ensuring the amplification of all voices; (3) the necessity for flexibility and the integration of continuous reflection; and (4) the pursuit of impact that transcends traditional academic outputs. Conclusion Participatory research and co-production are increasingly common approaches to research. These approaches have impacts on all stakeholders involved including co-researchers, public involvement practitioners, academic researchers and the wider community. In the context of this study, we demonstrate that undertaking co-production remotely and building meaningful partnerships remains possible where teams build good rapport challenging traditional power structures. The team members affirmative experiences could potentially positively affect their future participation in research, whether as participants and/or as co-researchers, as well as informing the future research strategies and decisions of researcher investigators.